Persahabatan Sejati Dalam Islam - Peter Bruno Sarbini (Sekolah Tinggi Widya Sasana, 2020)
A friendship in Islam is important. Even, a Muslim is suggested to be careful whom s/he is friends with. Making friends with the pious, good, right, honest, and other virtuous characters, will last forever to heaven. Only the prudent is able to be friends until heaven. The Quran emphasizes that friendship is not limited worldly relationship only, but it also determining our position in hereafter life (QS. az-Zukhruf: 67). A Muslim can meet everyone, but to make friends, make sure your friend is faithful (QS al-Maidah: 51, HR. Abu Daud, Tirmidzi). How precious to have a friend is. There are many verses in Quran and the SAW Prophet’s sunnah which contains the study of friendship.